The Role of Entrepreneurship in Promoting Local Economic Growth in Indonesia - Susi Sugiyarsih (Sultan Publisher, 2024)
Entrepreneurship is generally acknowledged as a major engine of economic development, especially at the local level. In Indonesia, the growth of entrepreneurial activity has resulted in the formation of businesses, the generation of jobs and the spread of economic opportunities in urban and rural areas. Entrepreneurship is increasingly being seen as a powerful tool for the promotion of productive economic activities and community well-being. As local governments continue to seek strategies to bolster regional economies, entrepreneurship has become an important piece of local economic development. In this paper, we examine the role of entrepreneurship in enhancing local economic growth in Indonesia. The study uses the approach of the narrative literature review by reviewing academic publications, policy documents, government reports and other relevant literature on entrepreneurship, small and medium-sized enterprises (SMEs), employment and local economic development. The collected literature was analyzed to find out the contribution of entrepreneurial activities to job creation, income generation, business development and regional economic performance. The discussion shows that entrepreneurship contributes to local economic growth by creating new business opportunities, expanding employment and using local resources. In addition, the development of SMEs contributes to strengthening economic resilience and increasing the participation of communities in economic activities. Access to capital, entrepreneurial skills, technology adoption and market access continue to be a challenge for business growth. Therefore, improving entrepreneurship entails supportive policies, capacity-building programs, improved access to finance, and the establishment of an enabling business environment. Entrepreneurship remains a vital tool in fostering sustainable local economic growth and improving socio-economic development in Indonesia.